POLITICAL NETWORKS ON TWITTER: Tweeting the Queensland state election - Bruns, A.; Highfield, Tim (2013)
This paper examines patterns of political activity and campaigning on Twitter in the context of the 2012 election in the Australian state of Queensland. Social media have been a visible component of political campaigning in Australia at least since the 2007 federal election, with Twitter, in particular, rising to greater prominence in the 2010 federal election. At state level, however, they have remained comparatively less important thus far. In this paper, uses of Twitter in the Queensland campaign from its unofficial start in February through to the election day of 24 March 2012 are tracked. Using innovative methodologies for analysing Twitter activities, developed by the research team, this study examines the overall patterns of activity in the relevant hashtag #qldvotes, and tracks specific interactions between politicians and other users by following some 80 Twitter accounts of sitting members of parliament and alternative candidates. Such analysis provides new insights into the different approaches to social media campaigning which were embraced by specific candidates and party organizations, as well as an indication of the relative importance of social media activities, at present, for state-level election campaigns. © 2013 Copyright Taylor and Francis Group, LLC.